Few‐Unit‐Cell MFI Zeolite Synthesized using a Simple Di‐quaternary Ammonium Structure‐Directing Agent. Issue 35 (1st August 2021) - Lu, Peng; Ghosh, Supriya; Dorneles de Mello, Matheus; Kamaluddin, Huda Sharbini; Li, Xinyu; Kumar, Gaurav; Duan, Xuekui; Abeykoon, Milinda; Boscoboinik, J. Anibal; Qi, Liang; Dai, Heng; Luo, Tianyi; et al.
Abstract: Synthesis of a pentasil‐type zeolite with ultra‐small few‐unit‐cell crystalline domains, which we call FDP (few‐unit‐cell crystalline domain pentasil), is reported. FDP is made using bis‐1, 5(tributyl ammonium) pentamethylene cations as structure directing agent (SDA). This di‐quaternary ammonium SDA combines butyl ammonium, in place of the one commonly used for MFI synthesis, propyl ammonium, and a five‐carbon nitrogen‐connecting chain, in place of the six‐carbon connecting chain SDAs that are known to fit well within the MFI pores. X‐ray diffraction analysis and electron microscopy imaging of FDP indicate ca. 10 nm crystalline domains organized in hierarchical micro‐/meso‐porous aggregates exhibiting mesoscopic order with an aggregate particle size up to ca. 5 μm. Al and Sn can be incorporated into the FDP zeolite framework to produce active and selective methanol‐to‐hydrocarbon and glucose isomerization catalysts, respectively. Abstract : A simple di‐quaternary ammonium cation was used as structure‐directing agent to prepare few‐unit‐cell (ca. 10 nm) MFI type zeolite catalysts and adsorbents with a wide range of composition (pure silica, aluminosilicate and stannosilicate). The SDA design was selected based on simple heuristic arguments regarding contributions of its structural elements to early crystal growth characteristics of MFI.